Effect of Combination between the Extract of Marsilea crenata and Alpinia purpurata K.Schum Rhizome on Sperm Quality of Hyperglycemia Mice - Shofi Nur Aliyah; Sri Rahayu; Agung Pramana Warih Marhendra (The Journal of Experimental Life Science, 2023)
This study aims to analyze the effect of the combination between water clover (Marsilea crenata) and red galangal rhizome (Alpinia purpurata) on sperm quality of hyperglycemia model mice. Mus musculus were randomly divided into eight groups: non-hyperglycemia (P0), hyperglycemia (P1), metformin 0.375 mg.kg-1 (P2), hyperglycemia with M. crenata extract dose 0.09 mg.g-1 (P3), A. purpurata dose 0.20 mg.g-1 (P4), combination of M. crenata (0.09 mg.g-1) - A. purpurata (0.20 mg.g-1) (P5), combination of M. crenata (0.09 mg.g-1) - A. purpurata (0.40 mg.g-1) (P6), and combination of M. crenata (0.18 mg.g-1) - A. purpurata (0.20 mg.g-1) (P7). Hyperglycemia mice were induced by streptozotocin 145 mg.kg-1. STZ induction and oral extract addition were carried out for 20 days. Sperm quality parameters observed in this study included motility, viability, and concentration. Sperm quality data were statistically analyzed with One-Way ANOVA followed by the Tukey HSD test using the SPSS 23 for Windows program (p<0.05). This research demonstrates that adding M. crenata, A. purpurata, and their combination for 20 days can significantly increase motility, viability, and sperm concentration in hyperglycemia-model mice. The combination of M. crenata and A. purpurata in the ratio of 1:1 was considered effective in improving the sperm quality of hyperglycemia model mice. Keywords: A. purpurata, hyperglycemia, M. crenata, oxidative stress, sperm quality.